Entropy analysis of unsteady magnetohydrodynamic nanofluid over stretching sheet with electric field - Daniel, Y. S. (Begell House Inc., 2017)
This paper reports the unsteady magnetohydrodynamic (MHD) natural convection flow of nanofluid over a permeable stretching sheet with buoyancy effects. Effects of Brownian motion and thermophoresis using a revised model are present. Entropy and heat transfer analysis is performed in the presence of viscous dissipation, Joule heating, and chemical reaction. Transformations techniques are applied to the constituted governing boundary layer equations to obtain a nonlinear couple of ordinary differential systems. Thereafter, the Keller-Box numerical method is applied to solve the problem and excellent agreement was found with those reported in the literature. The results corresponding to the velocity, temperature, concentration profiles, entropy generation and Bejan numbers profiles, tabular form for the skin friction, and the reduced Nusselt number for various pertinent parameters are examined. As the main outcome, our results show that on the flow field magnetic and electric fields exhibit opposite behavior; Hartmann number, Reynolds number, dimensionless Brinkman group, constant entropy parameter, and dimensionless group parameter intensify with entropy generation. Furthermore, thermal radiation, electric field, and Hartmann number gain the Bejan number.